Molecular and Antioxidant Characterization of Opuntia robusta Fruit Extract and Its Protective Effect against Diclofenac-Induced Acute Liver Injury in an In Vivo Rat Model - Gloria Stephanie Villa-Jaimes; Han Moshage; Francisco Javier Avelar-González; Herson Antonio González-Ponce; Manon Buist-Homan; Fidel Guevara-Lara; Esperanza Sánchez-Alemán; Sandra Luz Martínez-Hernández; Javier Ventura-Juárez; Martín Humberto Muñoz-Ortega; Ma. Consolación Martínez-Saldaña (MDPI AG, 2023)
A molecular characterization of the main phytochemicals and antioxidant activity of Opuntia robusta (OR) fruit extract was carried out, as well as an evaluation of its hepatoprotective effect against diclofenac (DF)-induced acute liver injury was evaluated. Phenols, flavonoids and betalains were quantified, and antioxidant characterization was performed by means of the ABTS•+, DPPH and FRAP assays. UPLC-QTOF-MS/MS was used to identify the main biocompounds present in OR fruit extract was carried out via. In the in vivo model, groups of rats were treated prophylactically with the OR fruit extract, betanin and N-acteylcysteine followed by a single dose of DF. Biochemical markers of oxidative stress (MDA and GSH) and relative gene expression of the inducible antioxidant response (Nrf2, Sod2, Hmox1, Nqo1 and Gclc), cell death (Casp3) and DNA repair (Gadd45a) were analyzed. Western blot analysis was performed to measure protein levels of Nrf2 and immunohistochemical analysis was used to assess caspase-3 activity in the experimental groups. In our study, the OR fruit extract showed strong antioxidant and cytoprotective capacity due to the presence of bioactive compounds, such as betalain and phenols. We conclude that OR fruit extract or selected components can be used clinically to support patients with acute liver injury.